2022
DOI: 10.3390/su14052992
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Sustainable Maintenance Strategies for Single Component and Multicomponent Equipment

Abstract: Contemporary industrial equipment is increasingly developing towards complexity. In order to ensure the high reliability and sustainability of industrial equipment, more flexible maintenance strategies have attracted extensive attention. In view of this, this paper aims to summarize the current situation of existing maintenance strategies, so as to enable colleagues in the industry to choose or formulate more efficient maintenance strategies. Firstly, the characteristics, application potential and limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 165 publications
0
19
0
1
Order By: Relevance
“…As mentioned earlier, all the methods were used to train on fused signals data. To assess the resulting models, multi-class confusion matrices were computed and Cohen's Kappa (K) was measured according to Equation (1). See the confusion matrices in Figure 11, where the column at the far right of the plot shows the precision, the row at the bottom of the plot shows the recall, and the cell at the bottom right of the plot shows the overall accuracy.…”
Section: Results Of Models Trained On Fused Sensor Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, all the methods were used to train on fused signals data. To assess the resulting models, multi-class confusion matrices were computed and Cohen's Kappa (K) was measured according to Equation (1). See the confusion matrices in Figure 11, where the column at the far right of the plot shows the precision, the row at the bottom of the plot shows the recall, and the cell at the bottom right of the plot shows the overall accuracy.…”
Section: Results Of Models Trained On Fused Sensor Datamentioning
confidence: 99%
“…Many industries still use time-based maintenance, which is maintenance performed at fixed time intervals according to a schedule. It is costly because it could lead to unnecessary maintenance when the machines do not encounter any problem [1].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study have revealed that for a project manager to oversee major maintenance projects in the energy sector successfully, that project manager must possess the technical experience and engineering skills in this sector. The objectives of any maintenance strategy include a complete balance between capacity, efficiency, availability, reliability, and maintenance costs (Zhao et al, 2022), appropriate to the industrial and economic environment in which the particular plant operates. This further implies that the project manager must also possess some local site-based knowledge, especially regarding the maintenance of power plants.…”
Section: Discussionmentioning
confidence: 99%
“…Within API manufacturing, the increased dependence on equipment has prompted the requirement to keep equipment in good condition [ 45 ] . Maintaining equipment in good condition requires a robust maintenance program with multiple manual and automated tasks [ 46 ].…”
Section: Literature Reviewmentioning
confidence: 99%